Effects of an Early Breastfeeding Education and Proactive Telephone Support Program for Mothers of Preterm Infants: A Quasi-experimental Study - Saehoong, Sutasinee; Pookboonmee, Renu; Daramas, Tipawan; Chansatitporn, Natkamol; Nuntnarumit, Pracha (Pacific Rim International Journal of Nursing Research, 2024)
Breast milk is optimal for both term and preterm infants as it provides essential nutrition and immunity. However, mothers of preterm infants often have insufficient milk supply, resulting in low breastfeeding rates, including in Thailand, where this quasi-experimental study was undertaken. We investigated the effects of an early breastfeeding education and proactive telephone support program, including early breastfeeding education and proactive telephone support. This included breastfeeding outcomes, including total breast milk volume, duration of exclusive breastfeeding, and exclusive breastfeeding rates at discharge and three months post-discharge in mothers of preterm infants. The participants included 57 mother-infant dyads and their families. The participants were assigned to either the control group (n = 28) receiving routine care or the experimental group (n = 29) receiving the intervention program. The assignment was done using purposive sampling and matching the number of pregnancies and gestational age between the two groups. Data were collected using the Demographic Characteristics Questionnaire, the Breast Milk Expressing Record Form, the Oral Care with Breast Milk Record Form, and the Breastfeeding Practice and Problems Record Form. Data analysis was performed using the chi-square test, Mann-Whitney U test, independent t-test, and descriptive statistics. The results indicated that, after receiving the program, the total breast milk volume from day 1 to day 7 and the duration of exclusive breastfeeding in the experimental group were significantly higher and longer than in the control group. At discharge, the rate of exclusive breastfeeding in the experimental group was higher than that of the control group but with no statistical difference. However, the experimental group had a significantly higher exclusive breastfeeding rate at three months than the control group. This study confirmed the program’s effectiveness in increasing the exclusive breastfeeding rate at three months. Nurses can integrate this program to promote breastfeeding as a critical component of preterm infant care. Still, a long-term follow-up study requires comprehensive testing of its effectiveness.